The Role of Digital Innovation in SMEs: A Financial Performance Perspective - Liana Mangifera; Farid Wajdi; Farah Amalia; Aulia Uswatun Khasah (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2022)
This research identifies the driving factors of SMEs' digital innovation and their effects on improving SMEs' financial performance during the COVID-19 pandemic, intending to discover the mediating role of digital innovation in improving SMEs' financial performance through innovation orientation, IT readiness, and digital capability. The type of research is quantitative with a sample of 188 SMEs actors in Surakarta and its surroundings who have adopted e-commerce and fintech, with SEM-PLS modeling analysis. The results show that digital innovation has an important role as a mediator for the variables of digital orientation, IT readiness, and digital capability that affect the improvement of SMEs' financial performance during the COVID 19 pandemic. SMEs that carry out digital innovation through e-commerce and fintech have increased financial performance compared to previously, this was seen from the percentage increase in sales and profits compared to the previous one. This research gives contribution to the new knowledge about the digital innovation of SMEs, the new conceptual framework that connects digital innovation with business performance from the perspective of financial performance. The significant positive effect of digital innovation on improving financial performance shows that it is important for small enterprise to improve their digitization skills and knowledge in business development to fulfill customer needs and improve performance for future business sustainability